Compassion fatigue and satisfaction in nurses and midwives during the covid-19 pandemic in Turkey - DEMİRGÖZ BAL, MELTEM (My University, 2022)
Objective: To examine the levels of compassion fatigue and compassion satisfaction of nurses and midwives during the COVID-19 pandemic and the influencing factors. Methods: This descriptive study was carried out with the participation of Turkish midwives and nurses. In the study using the convenience sampling method, data were collected online using an online questionnaire. The questionnaire, created through the Google form, was shared between May and June 2021 in the midwife and nurse groups (Facebook, Instagram, WhatsApp) on electronic platforms. Compassion fatigue (CF) and compassion satisfaction (CS) consisting of the burnout (BO) and secondary traumatic stress (STS) subcomponents were assessed by the Professional Quality of Life scale. The study was completed with 402 nurses and midwives from various units. Descriptive statistics, and the Mann-Whitney U and Kruskal-Wallis tests were used in the analysis of the data. Results: Among the participants, the rate of dissatisfaction with the clinic worked was 24.6% and the turnover intention rate was 70.6%. During the pandemic period, 75.6% of the participants reported that they were exposed to verbal violence, 7.7% to physical violence, and 74.4% to mobbing behaviors. Low CS was found in 24.9% of the participants, a high level of BO in 27.1%, and high STS in 32.8%. Conclusion: Violence and mobbing against nurses and midwives should be prevented in order to increase the professional quality of life.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Quality of Life; Burnout; Compassion Fatigue; Personal Satisfaction; Quality of Life; Burnout; Compassion Fatigue; Personal Satisfaction